Immunomagnetic separation combined with RT-qPCR for determining the efficacy of disinfectants against human noroviruses - Pengbo Liu; Myung Kim; David Schlesinger; Christine Kranz; Sangdo Ha; Jeehyoung Ha; James Slauch; Seungbum Baek; Christine Moe (Elsevier, 2015)
Summary: Little is known about the effectiveness of disinfectants against human noroviruses (NoV) partially because human NoV cannot be routinely cultured in laboratory. The objective of this study was to develop a NoV monoclonal antibody-conjugated immunomagnetic separation (IMS) procedure combined with real-time reverse transcription polymerase chain reaction (RT-qPCR) assays to study the in vitro efficacy of disinfectants against human NoV. Monoclonal antibodies against Norwalk virus (NV, GI.1) and NoV GII.4 were produced using unique NoV capsid proteins, and the antibodies were conjugated to magnetic Dynalbeads. The immunomagnetic beads were used to simultaneously capture intact NoV in samples and effectively remove PCR inhibitors. We examined the efficacy of ethanol, sodium hypochlorite, nine commercially available disinfectants, and one prototype disinfectant using the IMS/RT-qPCR. The sensitivity of this procedure was approximately 100 virus particles for both the NV and GII.4 viruses. The average log reductions in in vitro activities varied between disinfectants. The prototype disinfectant produced an average 3.19-log reduction in NV and a 1.38-log reduction in GII.4. The prototype disinfectant is promising of inactivating NoV. This method can be used to evaluate in vitro activity of disinfectants against human NoV. The IMS/RT-qPCR method is promising as an effective method to remove PCR inhibitors in disinfectants and enable the evaluation of the efficacy of disinfectants. Keywords: Disinfectant, Norovirus, Immunomagnetic separation, Real-time RT-PCR, PCR inhibition